Policing Desire : Pornography, AIDS and the Media. - Watney, Simon (Media and Society., 1997)
Since its initial publication, Policing Desire has proved to be an unparalleled analysis of "the cacophony of voices which sounds through every institution of our society on the subject of AIDS." For this third edition Simon Watney has provided a new preface, a compelling new concluding essay, and a directory for AIDS information that includes electronic resources.